P051 Immune phenotypes in acute severe ulcerative colitis. (30th January 2023) - Meringer, H; Canales-Herrerias, P; Jha, D; Livanos, A; Jougon, J; Cossarini, F; Tankelevich, M; Kayal, M; Colombel, J F; Mehandru, S
Abstract: Background: Acute Severe Ulcerative Colitis (ASUC) may occur in up to 25% of patients with UC during their disease course. Despite intensive in-hospital management, some patients still require colectomy. We aimed to define the mucosal immune phenotypes related to ASUC that associate with treatment-outcomes. Methods: Adult patients with ASUC (defined by Truelove and Witts criteria), (n=32) were recruited. UC patients (mild-moderate disease) (n=31) and normal volunteers (NV) (n=27) served as controls. Gastrointestinal (GI) biopsies from the left colon were analyzed by multiparameter flow cytometry (FC) for myeloid cells (classical and non-classical monocytes, dendritic cells), lymphoid cells (T cells, B cells) and innate (Natural Killer) cells. Therapeutic non-response was defined as surgery within 3 months of admission. Results: Six of the ASUC patients (18.8%) required colectomy during index admission and 8 (25%) within 3 months of admission, i.e. non-responders. Only 14/32(44%) patients were bio naïve on admission. Clinical parameters significantly associated with treatment non-response included lower hemoglobin and albumin levels (Fig. 1A). Significantly higher frequency of classical (CD14+) and non-classical (CD16+) monocytes as well as proliferating CD4+ and CD8+ cells were seen in ASUC compared to NV and UC patients with Mayo 1, 2, 3 inflammation (Fig. 1B). Furthermore, ASUC patients who were non-responsive to medical treatment had higher frequencies of CD14+ monocytes and proliferating (Ki67+) CD4+ T cells in the colon compared to medical treatment responders (Fig 1C). Conclusion: High frequencies of CD14+ monocytes and proliferating CD4+ T cells in the colon represent distinct immune signatures that relate to ASUC outcomes. Clinical trials targeting adverse clinical and immune phenotype-associated ASUC patients with combination therapies are warranted.